A Transitory Regime Water Supply in Conakry, Guinea - Clarke, George (The World Bank, 1999)
June 2000 - In several ways, the reform introduced to the water sector in Conakry, Guinea, in 1989 under a World Bank-led project was remarkable. It showed that even in a weak institutional environment, where contracts are hard to enforce and political interference is common, private sector participation can improve sector performance. Why did the sector improve as much as it did, and what has inhibited reform? Both consumers and the government benefited from reform of the water system in Conakry, Guinea, whose deterioration since independence had become critical by the mid-1980s. Less than 40 percent of Conakry's population had access to piped water - low even by regional standards - and service was intermittent, at best, for the few who had connections. The public agency in charge of the sector was inefficient, overstaffed, and virtually insolvent. In several ways, the reform introduced to the sector in 1989 under a World Bank-led project was remarkable. It showed that even in a weak institutional environment, where contracts are hard to enforce and political interference is common, private sector participation can improve sector performance. Ménard and Clarke discuss the mechanisms that made progress possible and identify factors that inhibit the positive effects of reform. Water has become very expensive, the number of connections has increased very slowly, and conflicts have developed between SEEG (the private operator) and SONEG (the state agency). Among the underlying problems: · The lack of strong, stable institutions. · The lack of an independent agency capable of restraining arbitrary government action, regulating the private operator, and enforcing contractual arrangements. · The lack of adequate conflict resolution mechanisms for contract disputes. · Weak administrative capacity.